Useful Platelet Indices for the Diagnosis and Follow-Up of Patent Ductus Arteriosus - Guler Kazanci, Elif; Buyuktiryaki, Mehmet; Unsal, Handan; Tayman, Cuneyt (American Journal of Perinatology, 2019)
Objective The aim of this study was to assess the utility of early postnatal platelet indices in the prediction of hemodynamically significant patent ductus arteriosus (hsPDA) and its response to pharmacological treatment in preterm infants.Study Design The medical records of 971 infants with gestational age < 30 weeks and birth weight < 1,500 g were analyzed retrospectively. Infants with hsPDA comprised the study group and those without hsPDA comprised the control group. Complete blood count results were recorded, and red cell distribution width-to-platelet ratio (RPR) and platelet mass were calculated.Results A total of 481 infants, 169 in the hsPDA group and 312 in the control group, were included. In terms of platelet indices, the hsPDA group showed significantly lower mean platelet volume (MPV) and platelet mass, whereas RPR was significantly higher (p < 0.05, respectively). Multiple logistic regression analysis showed that RDS (relative ratio [RR]: 2.39; 95% confidence interval [CI]: 1.45–3.93; p < 0.001), MPV < 7.85 (RR: 3.71; 95% CI: 2.29–6.01; p < 0.001), and RPR > 0.070 (RR: 5.33; 95% CI: 3.28–8.65; p < 0.001) were independent risk factors for hsPDA.Conclusion Low MPV and platelet mass and high RPR in the first hours of life are risk factors for hsPDA and hsPDA refractive to pharmacological treatment with ibuprofen in preterm infants.
Keywords: mean platelet volume; patent ductus arteriosus; platelet mass; red cell distribution width to platelet ratio